Micro structural and static structural analysis of LM6/B4C and LM6/B4C/GR hybrid aluminium metal matrix composites - Faisal, M.H.; Prabagaran, S. (International Journal of Engineering and Technology, 2017)
This research work was performed to interpret the fabrication and mechanical characteristics of LM6/B4C and LM6/B4C/Gr aluminium matrix composites. The aluminium matrix composites were manufactured by reinforcing B4C particles with varying wt % of 3, 5, 7 using stir casting technique. LM6/B4C 7% composite was made hybrid by adding 2% Graphite into it. The presence of graphite in such composites provide the self-lubricating effect, replacing conventional sliding contacts (bearings, sheaves, pistons, pulleys) with them. This also helps to reduce the lubricating oil and fuel consumption along with environmental benefits reducing energy wastage in industrial and automotive components. The properties of the composites were collated with the base alloy to analyse the enhancement in mechanical characteristics that had been transmitted by the reinforcement particles to the composites. The specimen microstructure was inspected using an optical microscope to ensure the uniform distribution of reinforcement particles in the matrix. The piston was modelled in CREO and using ANSYS 14.5 workbench static structural analysis of LM6 alloy, LM6/B4C composite and LM6/B4C/Gr hybrid aluminium composites are executed. Compared to LM6 alloy, better static structural properties were obtained in composites and hybrid composite.